Perilaku Kelompok Dalam Organisasi - Si’in Si’in; Kasful Anwar; Jamrizal (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Groups are part of human life. Every day people will be involved in group activities. Likewise, groups are part of organizational life. In organizations you will find many of these groups. Almost in general, people who are members of large or small organizations have a very strong tendency to seek familiarity in certain groups. Starting from the similarity of work tasks carried out, the closeness of the place of work, the frequency of meeting each other, and perhaps the similarity of shared pleasures, then closeness to each other arises. Start them grouping in certain organizations. To continue the material, we will discuss it with the following problem formulation.